Decoupled Django : understand and build decoupled Django architectures for Javascript front-ends - Gagliardi, Valentino (Apress, 2021)
Apply decoupling patterns, properly test a decoupled project, and integrate a Django API with React, and Vue.js. This book covers decoupled architectures in Django, with Django REST framework and GraphQL. With practical and simple examples, you'll see firsthand how, why, and when to decouple a Django project. Starting with an introduction to decoupled architectures versus monoliths, with a strong focus on the modern JavaScript scene, you'll implement REST and GraphQL APIs with Django, add authentication to a decoupled project, and test the backend. You'll then review functional testing for JavaScript frontends with Cypress. You will also learn how to integrate GraphQL in a Django project, with a focus on the benefits and drawbacks of this new query language. By the end of this book, you will be able to discern and apply all the different decoupling strategies to any Django project, regardless of its size. You will: Choose the right approach for decoupling a Django project Build REST APIs with Django and a Django REST framework Integrate Vue.js and GraphQL in a Django project Consume a Django REST API with Next.js Test decoupled Django projects.